2015
DOI: 10.52842/conf.caadria.2015.673
|View full text |Cite
|
Sign up to set email alerts
|

Generative Design for Folded Timber Structures

Abstract: Folding structures belong to the group of lightweight structural systems, which often consist of polygonal elements like triangles or quadrangles. Folding structures whose construction is made out of cross-laminated timber (CLT) panels represent an innovative step in the timber industry, which has many advantages. CLT panels can be used simultaneously as supporting elements and as finishing building envelopes. There are many prefabrication possibilities, high efficient material consumption, low production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Any kind of sustainable information such as LCA (life cycle analysis) standards or others are not accepted in common CAD software. Visual programming languages for creating more sophisticated models are also useful [110,111], and advanced parametric software such as Grasshoper [112], Rhino, Generative Components [113] are being used to create parametric buildings and components. In the case of Rhino, the research conducted by [114] developed a plug-in for the 3D modelling software Rhinoceors at the Institute for Digital Economy in the construction and wood industries (IdBH), which avoided complex node intersections and reduced fabrication complexity for the manufacture flow of architectural forms from wood.…”
Section: Sustainable Design and Optimizationmentioning
confidence: 99%
“…Any kind of sustainable information such as LCA (life cycle analysis) standards or others are not accepted in common CAD software. Visual programming languages for creating more sophisticated models are also useful [110,111], and advanced parametric software such as Grasshoper [112], Rhino, Generative Components [113] are being used to create parametric buildings and components. In the case of Rhino, the research conducted by [114] developed a plug-in for the 3D modelling software Rhinoceors at the Institute for Digital Economy in the construction and wood industries (IdBH), which avoided complex node intersections and reduced fabrication complexity for the manufacture flow of architectural forms from wood.…”
Section: Sustainable Design and Optimizationmentioning
confidence: 99%
“…In the same study, it was found that the use of timber frames in multistorey buildings could reduce embodied carbon by 48% in comparison with steel and by 19% compared to concrete as the principal structural material. Moreover, timber is renewable and lightweight, with good thermal properties and a low carbon footprint (Svatoš-Ražnjevi c, 2022;Hens et al, 2021;Kunic et al, 2021;Ostrowska-Wawryniuk, 2021;Bukauskas et al, 2019;Stavric and Bogensperger., 2015;Daerga et al, 2014;Leskovar and Premrov, 2012;Weinand, 2009). Additionally, timber provides an agreeable indoor microclimate and has positive effects on the occupants of the building, while reducing stress (Ostrowska-Wawryniuk, 2021;Tarin et al, 2019;Leskovar and Premrov, 2012).…”
Section: Timber-based Buildingsmentioning
confidence: 99%
“…The Huffman grid origami pattern was used in the roof of a sketch building at the Hanover World Expo in 2000 and for the gate of the 2002 Turin Winter Olympics. Stavric et al [7] constructed an architectural sketch using the expansion pattern of Miura-ori origami and analyzed the bearing capacity of the structure by using finite element software. Falk et al [8] designed a temporary church in Saint Loup, France, and optimized the lighting of the building through Autodesk Ecotect Analysis software, which was also based on the Miura-ori origami pattern.…”
Section: Introductionmentioning
confidence: 99%